WEB CIBERSECURITY - Danger of PHP Code Injection Vulnerability - Brandao, Pedro Ramos (Transactions on Engineering and Computing Sciences, 2020)
This work demonstrates that the use of laboratories for the development of curricular work in the area of information technology exclusively supported by cloud computing technology does not decrease the level of learning and assessment objects on the part of students. This scenario arose due to the need to interrupt face-to-face classes in physical laboratories due to the COVID-19 Pandemic. The study had as universe a master’s degree in Computer Science.